2013
DOI: 10.3389/fmicb.2013.00321
|View full text |Cite
|
Sign up to set email alerts
|

Current scenario of peptide-based drugs: the key roles of cationic antitumor and antiviral peptides

Abstract: Cationic antimicrobial peptides (AMPs) and host defense peptides (HDPs) show vast potential as peptide-based drugs. Great effort has been made in order to exploit their mechanisms of action, aiming to identify their targets as well as to enhance their activity and bioavailability. In this review, we will focus on both naturally occurring and designed antiviral and antitumor cationic peptides, including those here called promiscuous, in which multiple targets are associated with a single peptide structure. Emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 232 publications
(218 reference statements)
1
122
0
5
Order By: Relevance
“…It also possesses various biological functions like inhibition of lipopolysaccharide related inflammatory, immunomodulation and immunosuppressant activity (Mulder et al, 2013). Along with the above mentioned functions, antibiotic resistance evolution in using conventional antibiotics makes cationic antimicrobial peptides a better replacement for conventional antibiotics in semen extenders for cryopreservation (Zasloff, 2016).…”
Section: Cationic Antimicrobial Peptides (Camps)mentioning
confidence: 99%
“…It also possesses various biological functions like inhibition of lipopolysaccharide related inflammatory, immunomodulation and immunosuppressant activity (Mulder et al, 2013). Along with the above mentioned functions, antibiotic resistance evolution in using conventional antibiotics makes cationic antimicrobial peptides a better replacement for conventional antibiotics in semen extenders for cryopreservation (Zasloff, 2016).…”
Section: Cationic Antimicrobial Peptides (Camps)mentioning
confidence: 99%
“…Reviews available in the literature provide detailed description of the many different mechanisms underlying cancer cell toxicity (Gaspar et al 2013;Harris et al 2013;Hoskin and Ramamoorthy 2008;Papo and Shai 2005;Mulder et al 2013). Studies on structureactivity relationship have shown that some ACPs share with AMPs the ability to disrupt cell membranes, causing poration or micellization, and additionally inducing necrosis and/or apoptosis (Bhutia and Maiti 2008;Papo and Shai 2005).…”
Section: Mechanisms Of Action Cellular Targets and Selectivity Of Anmentioning
confidence: 99%
“…Also know as anticancer peptides (ACP) and host defense peptides (HDP) they also represent important candidates as novel drugs and have been carefully addressed in the current issue. For instance, cationic peptides have been considered as anticancer agents for presenting numerous advantages over chemical agents such as higher specific cytotoxicity to tumor cells, lower side effects and easier absorption as recently listed (Mulder et al, 2013). Diverse studies have shown that cancer cells are more anionic than normal cells.…”
mentioning
confidence: 99%